Economic factors of the competitive graduates formation in the continuous innovative education system in Ukraine - YESAULOV, Yuriy (Ways to Improve Construction Efficiency, 2025)
In the context of global competition and rapid technological advancements, graduates of educational institutions must demonstrate a high level of competencies, which largely depends on the financial resources invested in the system of continuous innovative education by both the state and private sector. This issue has become particularly relevant in Ukraine due to the full-scale war, which has led to increased youth migration, brain drain, and financial losses for the economy caused by reduced tax revenues and declining labor productivity. The study analyzes the key economic factors influencing the competitiveness of graduates in the system of continuous innovative education, including the level of state education funding, social inequality, access to further education, regional employment indicators, the quality of secondary education, and the investment attractiveness of different regions. The findings indicate that ensuring financial support for educational infrastructure, adapting curricula to labor market needs through the integration of digital technologies and artificial intelligence, and improving school safety measures are critical for enhancing the quality of youth training within continuous innovative education. Additionally, international grants and budget allocations aimed at improving digitalization, infrastructure, and vocational training programs contribute to strengthening graduates’ competitiveness. The paper underscores the necessity of developing financially sound educational policies in the system of continuous innovative education that optimize budget expenditures, ensure sustainable human capital development, and facilitate the successful integration of competitive graduates into the labor market while maximizing economic returns. Furthermore, the war has increased the financial burden on the state budget due to the urgent need to invest in school safety measures, such as shelter construction, which has become an essential aspect of funding continuous innovative education. The research findings highlight the importance of conducting a thorough economic and financial analysis to assess their impact on graduates’ competitiveness as a fundamental basis for Ukraine’s future labor potential and financial stability.